Reformulation on Fiducia Security Enforcement Law in the Framework of Ease of Doing Business - Senen, Ibrahim (Universitas Pelita Harapan, 2025)
Banks and non-bank financial institutions as distributors of funds to the public through credit (financing) to customers (debtors) using non possessory movable goods (known as fiducia security) as security. The existence of fiducia security has problems in terms of the enforcement that affect the ease of doing business. This research was conducted with the aim of analyzing the rules of enforcement of fiducia security and the implementation of these rules, starting from the problems that occur in the field, the factors that cause these problems to occur and the proposed solutions. The final objective of this research is to find an ideal formulation (reformulation) of the rules of enforcement of fiducia security in line with the needs of the business practice, which can be implemented so as to support the ease of doing business. The research method used is normative legal research with several approaches, namely statutory, conceptual, historical, comparative, and case approaches. The results of the research show that there is a need for improvement in the fiducia security enforcement system starting from the registration stage to the enforcement. The ultimate goal of the improvement is the creation of a fast, efficient and low-cost fiducia security enforcement system. The creation of the ultimate goal of improvement will have an impact on business ease, where from the debtor's perspective, it will be easy to access financing, while from the side of banks and non-bank financial institutions there would be a certainty in relation to the repayment of the channeled financing, which ultimately leads to the ease of doing business for all parties.